Inhabiting the Skin: Bodily Histories in Colum McCann’s Transatlantic - Guanaes, Alvany (Cadernos de Literatura Comparada, 2019)
This essay intends to analyze how the body is represented to signify History and histories through the characters in the novel Transatlantic (2013), written by acclaimed Irish author Colum McCann. On the one hand, taking into account the “political economy of the body” postulated by Michel Foucault, the body may be understood as a space of social, political and historical inscription. On the other, bringing the work of Didier Anzieu about the skin ego to a literary approach, the human corporeal presence may also be taken as the mediator between History and the subjective historical experience. In Transatlantic, more precisely on the chapter entitled “1845-46 – Freeman”, McCann writes about the crossing of the Atlantic done by the orator, writer, and abolitionist Frederick Douglass, also a fugitive slave, to a famine-devastated Ireland, hoping to win his freedom in this journey. Douglass marveled at the whiteness of the Irish skin as much as he was estranged for his being black. Personal, social, and historical issues are learned and resignified by the protagonist in this encounter, which is precisely the discussion focus of the present work.